Keefektifan Konseling Kelompok Cognitive Behavior Teknik Cognitive Restructuring Untuk Meningkatkan Body Image Positif Siswa SMA - Chairunissa, Eersta Tegar; Santoso, Djoko Budi; Utami, Nugraheni Warih (citeus, 2025)
Body image is a form of individual perception or assessment of body condition including body size and shape. The student's body image shows a position in the negative range. The behavior shown includes students being embarrassed if they leave the house without wearing a mask, embarrassed if they talk about acne, feeling dissatisfied with their less than ideal body shape and height. The research aims to test the effectiveness of cognitive restructuring technique group counseling in improving high school students' negative to positive body image. One Group Pretest-Posttest research design. The sampling technique was purposive sampling, and 5 students were obtained who had a negative body image category. Data collection uses a body image scale. Data were analyzed using the Wilcoxon test. The analysis results show a sig value. = 0.042 in the research subject, which indicates that the probability is smaller than the significance value α = 0.05, thus it can be concluded that H0 is rejected and H1 is accepted. It can be concluded that cognitive behavior group counseling with the Cognitive Restructuring technique is effective in increasing students' positive body image.